O mito do professor-educador: análise de uma evidência - Santos, Reinaldo Dias Dos [UNIFESP] (2020)
This research analyzes the mythification process of teaching work by the pedagogical discourse materialized in the specialized press. For that, we mobilized the French Discourse Analysis (AD) in interaction with Barthes’s studies on the concept of myths. We start from the hypothesis that the pedagogical discourse works as a memory operator, mythicizing teacher’s work by the figure of the educator. In fact, this mythicizing process mitigates historical contradictions and tends to naturalize the meaning of teacher’s job. Through discursive sequences collected in Revista Nova Escola, we track the different updates of the basic statement “every teacher is / should be an educator”. Through this guiding thread, positivity is produced in the second term (educator) to the detriment of the first (teacher). Hence a pre-admitted discursive truth emerges, namely, that every teacher is / should be an educator. The magazine is an important means of communication specialized in pedagogical discussions and aims to assist teachers in lesson planning, discussions about didactic and methodological interventions, in addition to promoting school training courses. Editorial texts from the section entitled “Dear Educator” published in the years 2016 and 2017 were analysed. This was an opportune moment when the national curriculum proposal was discussed: the BNCC (Common National Curricular Basis). Thus, our analysis demonstrates that the pedagogical discourse establishes an interdiscursive relationship with the religious in the mythification of being an educator - professional destined to exercise the profession as a mission, as a gift - as an imperative to be a teacher.